Health behavior change Moving from observation to intervention [article]. - Sheeran, Paschal
How can progress in research on health behavior change be accelerated? Experimental medicine (EM) offers an approach that can help investigators specify the research questions that need to be addressed and the evidence needed to test those questions. Whereas current research draws predominantly on multiple overlapping theories resting largely on correlational evidence, the EM approach emphasizes experimental tests of targets or mechanisms of change and programmatic research on which targets change health behaviors and which techniques change those targets. There is evidence that engaging particular targets promotes behavior change; however, systematic studies are needed to identify and validate targets and to discover when and how targets are best engaged. The EM approach promises progress in answering the key question that will enable the science of health behavior change to improve public health: What strategies are effective in promoting behavior change, for whom, and under what circumstances? -- (from the author)
Keywords: Experimental medicine; Interventions; Trials; Theory; Construct; Correlational data